Impact of grass silage quality on greenhouse gas emissions from dairy and beef production. (28th May 2019) - Åby, Bente A.; Randby, Åshild T.; Bonesmo, Helge; Aass, Laila
Abstract: High‐quality grass silages may represent a mitigation option by reducing enteric methane production and by increasing productivity, thus reducing greenhouse gas emissions per kg of product (emission intensity). Two previous studies found considerable effects of three different silage qualities cut at different maturity stages (very early [H1], early [H2] and normal [H3]) offered ad libitum with various levels of concentrate supplementation, on animal performances of growing/finishing bulls and dairy cows in early lactation, indicating that emission intensities may also vary. Based on results from these previous studies, the aim of this study was to estimate emission intensities for milk and beef carcasses for the included combinations of silage qualities and concentrate levels, by using the farm‐scale model HolosNor. The emissions intensities were lowest for the H1 silage, and highest for the H3 silage, independent of concentrate levels for both milk and beef. Thus, increasing concentrate levels did not compensate for lower grass silage quality. Improvements in silage quality from H3 silage to H2 is realistic and has the potential to reduce emission intensities with approximately 10% while keeping the milk yield per cow constant and reducing the use of concentrates considerably. For beef production, the potential is even larger, with a reduction in emission intensity of approximately 17%. We conclude that improving grass silage quality may be a mitigation option that will also reduce the dependence on concentrates.